Estimating the impact of the 2012 liquor prohibition on crime - Krejsa, Jiří; Dušek, Libor; Koten, Silvester van, 1970-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This thesis focuses on capturing causal link between alcohol consumption and one of its externalities, crime. The quasi-natural experiment of the Czech temporary ban on hard liquor following an outbreak of methanol poisonings in September 2012 provides a valuable setting for evaluation of the alcohol-crime relationship. Over the course of the prohibition, violent crime rates fell by approximately 10 %, just like the aggregate of aggravated assault, criminal threatening, vandalism and property damage. In addition, the biggest share of reduction in crime falls on weekend criminality. The number of offenders under the influence of alcohol dropped by approximately 18 % for traffic-related offences and by 28 % in non-traffic offenses. The possibility of the reduction in crime being caused by lower detection capabilities of the law enforcement was examined. The reduction in reported cases of e.g. driving under the influence might be to a large extend explained by lower detection, but it could have reduced only rates of victimless crimes. Finally, the property crime rate was not significantly affected by the intervention, except for burglaries into bars and restaurants.
Vedoucí práce: Libor Dušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses